# Math

posted by .

27a4b7 (A-1)3
----------- • ------------ = ?
3a2-6a-3 9ab

• Math -

3a^2-6a-3 = 3(a-1)^2, so we end up with

27a^4b^7(a-1) / 27ab = a^3b^6/(a-1)

## Similar Questions

3a²-a-4=0 solving for the roots,
2. ### math

3a2-9ab+4b2-7ab=
3. ### math

I need help solving this subtraction (xy-ab-3)- (xy-9ab-1) the answe is __ab-___
4. ### math

sums and differences of rational algebraic expression please answer the following 9ab/cd^2 - 7ab/cd^2 another 3/x-1 - 2/x-1 another is 4x/4x-y - 2x/4x-y another is 3x/2y - 3x-2y/3x+2y another is 8/3x - 3/4x + 4/12x another is x-3/3x+1 …
5. ### math

3a2 - (3a - x + b)
6. ### math

DETER MINE THE PRODUCT OF THE FOLLOWING.1.(3Y+4X)(3Y-4X) 2.(p1/2Q)2 3.(A+BC)(2X-4B) 4.(X-1)(X2+2X+3) 5.(A+2B)(-3A2+2AB+2B2)
7. ### math

DETER MINE THE PRODUCT OF THE FOLLOWING.1.(3Y+4X)(3Y-4X) 2.(p1/2Q)2 3.(A+BC)(2X-4B) 4.(X-1)(X2+2X+3) 5.(A+2B)(-3A2+2AB+2B2)
8. ### math

be found arithmetic series 3a2-a6=-a2 a3+a4=19
9. ### Math

Find the HCF 1) 7x and 9 : nothing 2) x^2(x-4) and x(x-4) : its (x-4)?
10. ### math

The gradient of one of the line of ax2+2hxy+by2=0 is twice that of the other,show that 8h2=9ab

More Similar Questions